Saturated fatty acids and mortality in patients referred for coronary angiography: the Ludwigshafen risk and cardiovascular health study - Kleber, Marcus E.; Delgado Gonzales de Kleber, Graciela; März, Winfried (Journal of clinical lipidology, 2018)
Saturated fatty acids are thought to be harmful by increasing the risk for cardiovascular events. We examined the associations of erythrocyte saturated fatty acids with total and cardiovascular mortality in patients referred for coronary angiography.